TFF3 initiates gastric intestinal metaplasia by activating JAK2 and STAT3 under high salt conditions - Yanhong Wang; Feifei Qian; Baodong Shan; Li Zhang; Jie Zhong; Song Chen; Manman Yao; Shengnan Li; Xixiang Cao; Sujuan Fei; Xunlei Pang (Scientific Reports)
Abstract The mechanism underlying the role of trefoil factor family 3 (TFF3) in intestinal metaplasia remains unclear. This study reveals the molecular mechanism by which TFF3, in the process of gastric mucosal epithelial cell intestinal metaplasia (IM) induced by high salt, activates the JAK2/STAT3/CDX2 pathway, providing a potential target for the occurrence of IM. An in vitro model of high salt-induced intestinal metaplasia was established using bioinformatics to screen the GEO dataset for significantly differentially expressed genes related to intestinal metaplasia. The gastric epithelial cell line GES-1 was cultured in high-salt medium, and changes in cell function and the expression of TFF3, JAK2, STAT3, and CDX2 were examined following TFF3 knockdown or overexpression. Subsequent experiments disrupted the TFF3-JAK2/STAT3-CDX2 pathway to assess its effects on gene expression and cell function. The expression of TFF3 is upregulated during intestinal metaplasia, which promotes cell proliferation and migration. TFF3 regulates the expression of JAK2, STAT3, and CDX2 and activates the JAK2/STAT3 pathway to induce CDX2 expression in gastric epithelial cells, leading to intestinal metaplasia. Functional assays revealed that the TFF3-JAK2/STAT3-CDX2 pathway enhances both cell proliferation and migration. TFF3 induces intestinal metaplasia in gastric epithelial cells through the JAK2/STAT3-CDX2 pathway, providing new insights into the underlying mechanism and therapeutic strategies for intestinal metaplasia.